(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
Faced with the risks of approaching a subject so relevant to Portuguese literature, which further grounded its modernity in the novel, here a brief reflection on Neorealism in Portugal will be developed, including its character of militancy, denunciation and reflection, with writers of the stature of Alves Redol and Vergílio Ferreira, each in his own way, representing the impossibility of man detaching himself from his social dimension. More specifically, this proposition leads me to think about the existentialist phase of the author of Estrela Polar (1962), asking how far he would have departed even from the social realities propagated by the movement. For this course, I present two of the questions that interest me most: a) could the character Alberto, from the novel Aparição, as a Heideggerian “there-being”, make a difference for himself at first, aiming, after a while, to feel fit to embrace the collective? b) Could this be part of a kind of project by Vergílio Ferreira, who would thus qualify his work as an interchangeable whole? Thus, attuned to the main premise, critics such as João Laranjeira Henriques, José Carlos Barcellos, José Rodrigues Paiva, Isabel Margato and Carlos Reis lead me to believe that the rapprochement between the writers listed very well represents the design of prolific possibilities of comprehension/rereading of the literary works involved, highlighting the current events. Key words: Portuguese Neorealism, Existentialism, Alves Redol, Vergílio Ferreira.